Literature Review: Cardiac Complication Of Idiopathic Pulmonary Fibrosis - Dharmawan, Ibrahim N.I.P.; Muliawan, Hary Sakti; Nurwidya, Fariz (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2024)
Idiopathic pulmonary fibrosis (IPF) is a chronic, fibrosing interstitial pneumonia of unknown cause that is associated with radiological and histologic features of usual interstitial pneumonia (UIP). Idiopathic pulmonary fibrosis occurs primarily in adult and associated with poor prognosis with patients typically survive 2-3 years after diagnosis, although some cases progress much faster than others. Symptoms of IPF include cough and shortness of breath, especially during activity. In severe cases, respiratory failure may occur. IPF is often linked to several health problems, including lung cancer, sleep apnea, heart disease, and digestive issues like acid reflux. The cardiovascular problem related to IPF are pulmonary hypertension, coronary artery disease, arrythmia, and iatrogenic disease caused by IPF pharmacological treatment. This literature review will explain the link between IPF and its pathogenesis in causing cardiac complications based on available literature.